External and internal shame’s role in psychological health among people with and without chronic disease: Exploring mediating adaptive processes - Pina, Inês Carolina Andrade Matos (2019)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação